APPLICATION ANALYSIS OF THE INFORMATION SYSTEM FOR REPORTING IMMIGRATION PERMITS FOR PORT TRANSPORTATION EQUIPMENT AT THE IMMIGRATION OFFICE CLASS II TPI BELAWAN - Rasona S Akbar; Gunawan Ari Nursanto; Rainhard Bounkey Marbun (Polteknik Imigrasi, 2021)
At this time the earth is being hit by the Corona Virus pandemic which has resulted in a lack of direct interaction in services and in the field of immigration, especially in reporting services for immigration permits for transportation equipment / ships. This situation has the potential to be exploited by unscrupulous individuals to carry out unscrupulous acts such as extortion and other things. Then the immigration office made an innovation, namely the application of the Port Transport Equipment Immigration Permit Reporting Information System, which was abbreviated as Sili Laba. The aim of the researcher was to determine the profile of the Sili Laba application, and the effect of the Sili Laba Innovation Strategy on the performance of the Class II TPI Belawan immigration office. In this study using quantitative methods. And the results of the research based on the regression test show that Y = 37.549 + 0.331X which states that for every additional 1 value of the innovation strategy, the performance value will increase by 0.331. Based on the results obtained from the above equation, the calculated t value is greater than the t table value, which is 6.064 > 2.021. So, from the results of the above equation it can be concluded that there is an influence given by the innovation strategy variable (X) on the performance variable (Y).